Excavations at Tintagel Castle, Cornwall, 1990-1999 - Barrowman, Rachel C. (Reports of the Research Committee of the Society of Antiquaries of London, 2007)
Romantic rock-perched sea-girt Tintagel is a magical place that resonates with Arthurian associations - and the archaeological reality is no less intriguing than the legend. Investigation of the site began in the 1930s, when Dr Ralegh Radford uncovered remains of buildings with significant volumes of eastern Mediterranean and North African pottery of fifth- to seventh-century date, suggesting a western British site of iconic importance in the economy of the late Antique and Byzantine world. The research presented in this book comes from renewed fieldwork carried out at this promontory site over several seasons between April 1990 and July 1999, using modern archaeological techniques, together with previously unpublished work from Radford's private archive, along with that of his architect, J A Wright. This work has demonstrated the complexity and variability of building forms and associated occupation at the site and the wide-ranging connections of Tintagel during the fifth to seventh centuries, as reflected in the extensive ceramic assemblage, while re-examination of the 'Great Ditch' has established that this is the largest promontory or hill-top site of its period. A unique glass assemblage and a stone with a probable imperial inscription to Honorius - later the object of graffiti from three post-Roman personages, Paternus, Coliavus and Artognou - serve as dramatic testimony to the cultural and literary milieu of high-status Dumnonian society in the post-Roman period.